Effectiveness of the questionnaire investigations in the group of patients with high risk of the hereditary colorectal cancers - Markiewicz-Grochowalska, Agata; Kaluba-Skotarczak, Agnieszka; Niziołek, Aleksander; Grochowalski, Marcin; Golusiński, Piotr; Banasiewicz, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2003)
Colon cancer is one of the most common cancers, in 25% of cases the positive familial history is recognized. In the group of patients with hereditary colon cancers screening and presymptomatic clinical examination is very effective method in the prevention of the malignant transformation. Early detection of the high-risk patient is still not sufficient, one of the useful method may be questionnaire investigation. We analyzed 9000 patients hospitalized in the Central Regional Hospital in Poznań in 1996-2001. The malignant disease was recognized in 1805 patients, in 250 cases the age of diagnosis was below 50 years. In 94 cases at least one of the family members was treated due to malignant process. The questionnaire was sent to all these 94 patients. We received 35 completed questionnaires (37% of all questionnaires), after analysis of pedigree HNPCC was recognized in 8 cases (8.5% of the questionnaires), HNPCC-suspected in 17 cases (18% of the questionnaires). The patients with familial risk of the colorectal cancer were qualified to clinical control examinations. Questionnaire investigation of the patients may be a very useful method of the recognition of patients with familial risk of the colorectal cancer.